Macroeconomic’s effect on Islamic and conventional banking profitability: Evidence from Indonesian dual-banking system - Achmad Fadlil Abidillah; Roisatun Kasanah; Sulistya Rusgianto (Faculty of Economics, Universitas Islam Indonesia, 2022)
Purpose – This paper aims to analyze the effect of macroeconomic and global crisis variables on Islamic and conventional banking profitability, evidence from Indonesian dual-banking system.Methodology – Time-series data from 2008q1–2021q2 were analyzed using an Autoregressive Distributed Lag (ARDL) model. This method can describe both long run and short run equilibrium between banking profitability and macroeconomic variables.Findings – The results point out that in a long run model, sharia banking's profitability is more resistant to macroeconomics shock than conventional's. Then, in a short run model, sharia's ROA and conventional's ROA face different effects of economic growth, exchange rate, and global crisis. Sharia's NPM is more affected by macroeconomic variables than conventional's.Originality – This study used an ARDL model to develop a dynamic relation between macroeconomic variables and dual bankings profitability.